Detection of anti-M. leprae antibodies in healthy children in China: A systematic review of Chinese literature - Zhou, Zijie; Pierneef, Louise; van Hooij, Anouk; Geluk, Annemieke (Frontiers in Tropical Diseases, 2022)
Leprosy is an infectious disease caused by Mycobacterium leprae (M. leprae) that mainly involves the skin and peripheral nerves, causing lifelong deformities and social stigma. As evident from the practically stable number of new cases reported worldwide during the past decade, transmission is still ongoing. On route to leprosy elimination, an appropriate tool is needed to monitor M. leprae transmission. M. leprae-specific antibodies indicate infection with M. leprae, but do not differentiate between present and past infection. Nevertheless, detection of M. leprae infection in young children per definition indicates recent infection. Hence, seroprevalence in young children can be used to monitor recent M. leprae transmission. Despite having eliminated leprosy in most parts of the country, studies on transmission conducted in China are not sufficiently reported in the English literature. Therefore, we performed a systematic review of Chinese literature describing serological studies in healthy children in (former) leprosy endemic areas in China, available in the Chinese databases: China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), and Wanfang Database. From the 710 articles identified in these three Chinese databases, only four full-text articles fulfilled all inclusion criteria regarding sufficiently detailed descriptions of anti-M. leprae antibodies in healthy children. Two additional papers were identified through snowballing, resulting in a total of six articles considered for this review reporting quantitative serological data from three Chinese provinces between 1987 and 2003. All studies used ELISAs to quantify antibody levels. Seroprevalence in healthy children ranged from 7.93% (Yunnan) to 32.35% (Jiangsu). If the same method was used (in Jiangsu), direct comparison of studies at different time points indicated that decrease in disease prevalence (0.28 to 0.16 per 100,000) or new case detection rate (2.6 to 1.0 per 100,000) from 1987-1991 corresponded to decrease in anti-M. leprae antibody seroprevalence (30.86% to 22.61%) in healthy children. Thus, these findings are consistent with the previous finding that anti-M. leprae antibody seroprevalence in young children represents a surrogate indicator to monitor transmission.